1982
DOI: 10.1111/j.1526-4610.1982.hed2201038.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Data in Chronic Post‐traumatic Headache

Abstract: Twenty chronic post-traumatic headache subjects (16 men and 4 women) were considered, together with age and sex matched normal controls. Pituitary function was challenged by means of luteinising hormone releasing hormone (100 microg, i.v.), thyrotropin (TSH) releasing hormone (200 microg, i.v.) and regular insulin (.1 U/kg, i.v.). The responses of gonadotropins, TSH, somatotropin (STH) and prolactin (PRL) were studied in the group as a whole and in clinical subgroups. No differences were found in the baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1982
1982
2001
2001

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In the field of headache, we were able to show that the regulation of PRL secretion is altered in common migraine (7) and in catamenial headache (8). We also showed that changes in the regulation of pituitary hormones are present in chronic post-traumatic headache (9,10). Kudrow (11,12) demonstrated that the secretion of luteinizing hormone (LH) and of testosterone is altered in CH.…”
Section: Introductionmentioning
confidence: 82%
“…In the field of headache, we were able to show that the regulation of PRL secretion is altered in common migraine (7) and in catamenial headache (8). We also showed that changes in the regulation of pituitary hormones are present in chronic post-traumatic headache (9,10). Kudrow (11,12) demonstrated that the secretion of luteinizing hormone (LH) and of testosterone is altered in CH.…”
Section: Introductionmentioning
confidence: 82%
“…Accordingly, age‐adjusted TSH values were lower in headache sufferers, especially amongst migraineurs, than in those without headache complaints. This result differs from those of previous studies, which have been hospital‐based, and consisted of small series of patients with headache classified as cluster headache, migraine, or post‐traumatic headache (Savoldi et al. , 1982; Murialdo et al.…”
Section: Discussionmentioning
confidence: 99%
“…25 Recently, PRL has been used to study dopaminergic function in migraine. 26 Administration of dopamine-antagonist drugs such as sulpiride or domperidone in adult migraineurs (particularly women) causes a prolonged increase of plasma PRL compared to normal controls. On the contrary, administration of dopamine agonists does not cause the expected extent of decrease in plasma PRL in adult migraineurs.…”
Section: Discussionmentioning
confidence: 99%